Water quality, diversity and distribution of freshwater fishes in, Negeri Sembilan / Nur Hasyimah R. ... [et al.] - R., Nur Hasyimah; M.H., Syakira; M.Z, Mohd Syahril; A, Samat; I, Iwana (Universiti Teknologi MARA, Negeri Sembilan, 2013)
The study of diversity and distribution of freshwater fishes at Sungai Sungai Muar in Kuala Pilah, Negeri Sembilan was done on 30-31 January 2011. Cast net and trawl were used in the sampling activities. Species of fishes found during sampling activities includes Cyclocheilichthys apogon, Osteochilus hesseltii, Hampala microlepidota, Puntius gonionotus, Oreochromis mossambicus, Hyposarcus pardalis and Prophagorus nieuhofi. In Sungai Sungai Muar, fishes from family Cyprinidae was dominant with total of 24 individuals from 4 species which include Cyclocheilichthys apogon, Osteochilus hesseltii, Hampala microlepidota and Puntius gonionotus. Diversity and distribution of species was analyzed using diversity index which is Shannon-Weiner and Simpson Index. Based on the analysis provided, the reading shows that Sungai Muar consist of high diversity of fish species with diversity indexes 2.14 (Shannon-Weiner) and 0.75 (Simpson). The most abundant species at the site was Osteochilus hesseltii with 13 individuals while the least abundant species was Prophagorus nieuhofi with one individual only. For water quality observation, the mean of the following data was recorded as the following; temperature was 24.9 °C, the percentage of Dissolved Oxygen (DO) was 58.97 %, the conductivity of water was 68.27 µs and pH was 6.94. Based on the data, we can conclude that the condition of Sungai Muar in Kuala Pilah is Sungai Muar was classiffied as Class I which indicates suitable for very sensitive aquatic species.